Impact of an integrated youth skill training program on youth livelihoods: A case study of cocoa belt region in Ghana. (March 2022) - Unnikrishnan, Vidhya; Pinet, Melanie; Marc, Lukasz; Boateng, Nathaniel Amoh; Boateng, Ethel Seiwaa; Pasanen, Tiina; Atta-Mensah, Maya; Bridonneau, Sophie
Highlights: The study evaluates the impact of a multifaceted skills training program given to youths in Ghana. The strategies include adopting better agricultural practises, farming and cultivating cocoa. This also encompasses improvement in the saving behaviour and using formal institutions to save, income and employment. Young men are almost twice more likely to grow cocoa then young women. Skills training alone are not enough to affect overall youth employment participation in the cocoa value chain. Abstract: This paper assesses the impact of an integrated skills training program given to youth aged 17–25-year-old living under the 2/day poverty line in the cocoa belt region of Ghana. Despite being a leading producer of cocoa and having a burgeoning youth population, it is estimated that the average age of a cocoa farmer in Ghana is greater than 50 years. To introduce young people to cocoa farming and address the potential barriers they face in order to do that; a multi-faceted skills training programme was designed with the ultimate aim of improving and diversifying youth livelihoods. The training had three key components: i) cocoa academies (which includes agricultural practices; life skills and financial literacy); ii) business incubators (including entrepreneurial training, networks, mentoring) and iii) supporting enabling environment (access to land and finance). Combining quasi-experimental methods Propensity Score Matching with Difference in Differences, we estimate the causal effect of the programme on agricultural outcomes (farming, agricultural practices), financial behaviour outcomes (saving practices, mobile banking) and livelihood outcomes (employment, income, poverty likelihood) one year after the completion of training. The results of the impact evaluation suggest that compared to the control group (youth non-participants), youths who participated in the training adopt better agricultural practices (26 percentage points (pp)), cultivate cocoa (24 pp), and are more likely to engage in farming (22 pp). We also find a 28.7% increase in income in the last seven days and hours worked by 12.4%. Youth also increase the use of banks for saving (16 pp), save using mobile money (6.7 pp), the use of Village Savings and Loan Associations (1.7 pp) and, in general, the use of mobile money for both sending and receiving transfers (10.6 pp). The sex-disaggregated sub-sample analysis provides other valuable insights on the intervention.